Learning Loss Siswa dalam Pembelajaran Pendidikan Agama Islam (PAI) di SMPN 2 dan SMPN 4 Kota Sampit Kalimantan Tengah - Adengganan Harahap; Mazrur Mazrur; Setria Utama Rizal (Journal on Education, 2025)
This study aims to analyze the phenomenon of learning loss that occurs in Islamic Religious Education (PAI) learning at SMP Negeri 2 and SMP Negeri 4 in Sampit City, Central Kalimantan, particularly in the aspects of learning the Qur’an, Hadith, and Fiqh, which are important foundations for students in Islamic life. The decline in academic performance in PAI subjects is influenced by several factors, including the lack of family attention in guiding children's religious education, economic limitations that hinder access to religious education guidance, and students' difficulties in reading and memorizing the Qur’an correctly. This research uses a qualitative method with a descriptive approach, through interviews with teachers and school principals, as well as direct field observations. The results of the study show that the phenomenon of learning loss in PAI learning at both schools is closely related to internal and external factors that affect students' motivation and ability to follow the lessons. Efforts to address this issue include providing extra guidance, involving families in the religious education process, and optimizing learning at school using various appropriate methods. This study is expected to provide insights into the importance of cooperation between schools, families, and the community in improving the quality of religious education, particularly in overcoming learning loss.